Orientation on ‘Visions of the Good’: A Narrative Analysis of Life Stories of Patients with Personality Disorders - Sylvie P. de Kubber; Angelien Steen; Carmen Schuhmann; Arjan W. Braam (Religions, 2022)
Persons with a diagnosis of personality disorder struggle to experience meaning in life. This article explores how meaning in life of patients with personality disorder changes during intensive psychotherapy. In a qualitative study, life stories of nineteen Dutch patients receiving intensive psychotherapy, written both before and after treatment, were analyzed using holistic content analysis. Here, meaning in life was understood and operationalized in terms of the concept of orientation towards visions of the good by philosopher Charles Taylor. The findings suggest that patients experience both positive and negative shifts concerning meaning in life. On the one hand, in comparison to the first life stories, there is more awareness and insight about the way the ‘good’ is missing in the second life stories. On the other hand, there are more descriptions about being vulnerable, guilty or ashamed, whereas particular sources of meaning are missing.